Revealing the Formation Mechanism of CsPbBr3 Perovskite Nanocrystals Produced via a Slowed‐Down Microwave‐Assisted Synthesis. (19th April 2018) - Li, Yanxiu; Huang, He; Xiong, Yuan; Kershaw, Stephen V.; Rogach, Andrey L.
Abstract: We developed a microwave‐assisted slowed‐down synthesis of CsPbBr3 perovskite nanocrystals, which retards the reaction and allows us to gather useful insights into the formation mechanism of these nanoparticles, by examining the intermediate stages of their growth. The trends in the decay of the emission intensity of CsPbBr3 nanocrystals under light exposure are well correlated with their stability against decomposition in TEM under electron beam. The results show the change of the crystal structure of CsPbBr3 nanocrystals from a deficient and easier to be destroyed lattice to a well crystallized one. Conversely the shift in the ease of degradation sheds light on the formation mechanism, indicating first the formation of a bromoplumbate ionic scaffold, with Cs‐ion infilling lagging a little behind. Increasing the cation to halide ratio towards the stoichiometric level may account for the improved radiative recombination rates observed in the longer reaction time materials.